Combination of biological pretreatment with NaOH/Urea pretreatment at cold temperature to enhance enzymatic hydrolysis of rice straw. (December 2015) - Dai, Youzhi; Si, Mengying; Chen, Yuehui; Zhang, Nianlei; Zhou, Mo; Liao, Qi; Shi, Deqiang; Liu, Yine
Highlights: A novel pretreatment combined S. sp. LD-1 with NU was conducted. Rapid bacterial treatment reduced the requirements of NU treatment. Synergistic effect existed in the stepwise pretreatment for RS saccharification. Combination pretreatment resulted in significant increase of sugar yields. Abstract: A stepwise pretreatment of combination of bacterial treatment with NaOH/Urea (NU) treatment was conducted to enhance enzymatic hydrolysis of rice straw (RS). The results showed that the composition of RS changed significantly, the lignin and hemicellulose decreased while cellulose increased. The biological treatment with a bacterium Sphingobacterium sp. LD-1 achieved mild conditions for the sequential NU treatment, reducing the concentration of the NU solution from 7%/12% to 4%/6% and increasing the temperature from −20 °C to −10 °C. The saccharification of rice straw co-treated with bacterium Sphingobacterium sp. LD-1 and 4%/6% NU at −10 °C resulted in 1.396-fold and 1.372-fold increase of reducing sugar and glucose yield respectively than that of sole NU treatment.